Lectotypification of the genus Geissaspis Wight & Arn. (Fabaceae-Papilionoideae) - Balan, Anoop P.; Predeep, S.V.; Udayan, P.S.; Prakashkumar, R. (Bangladesh Journal of Plant Taxonomy, 2018)
Not available.